Measurement and Analysis of Dielectric Properties of Agricultural By-product Powders in Microwave Frequency Range - Zhong Runeng; Xiang Tai; Zheng Qinhong; Xu Bo (E3S Web of Conferences, 2019)
Dielectric properties play an important role in the microwave-assisted application of nonmagnetic agriculture-related media. In this paper, the practical requirements for the lack of quantitative data on the dielectric properties of agricultural media in microwave-assisted applications are obtained. The dielectric properties data of four kinds of agricultural by-products powder (Potato powder, Pseudo -ginseng Powder, Gastrodia elata powder, Dendrobium chrysotoxum Lindl powder) under microwave frequency were measured, and related factors were analyzed. The results show that the uncalibrated coaxial transmission reflection method can be used to measure and analyse the dielectric properties of high frequency bands of powder materials. Dielectric constant (ε ′) and Dielectric loss factor (ε '') of agricultural by-products at room temperature have a relationship between microwave frequency and moisture content. It is a dependent and the mathematical relation is satisfied. The influence of microwave frequency and moisture content on the dielectric properties is as follows: lows: ε′>ε′′>tanδ. Under the conditions of civil microwave frequency (2.45GHz) and moisture content (2% ~ 25%), the dielectric constant and the dielectric loss factor of different kinds of agricultural by-products powder are in the range of 3.5 ~ 9 and 0.1 ~ 3.2 respectively. The results provide data basis for microwave processing and quality monitoring of agricultural by-products powder. The technical method is suitable for the measurement and analysis of the dielectric properties of powder materials.